Portfolios of actively managed mutual funds. Issue 2 (1st February 2021) - Riley, Timothy B.
Abstract: Investors should focus on the performance of portfolios of active funds, not on the performance of individual active funds. Taking this portfolio approach with respect to active U.S. equity mutual funds, I build an optimized portfolio of funds that subsequently has low idiosyncratic volatility and a large, positive, statistically significant alpha. Consistent with a Berk and Green equilibrium, that outperformance is short lived if the optimized portfolio is not rebalanced often, as investors allocate substantial capital—in excess of that expected based on past performance—to the funds with a large weight in the optimized portfolio.